DEVELOPMENT OF EXCAVATION MATERIAL CHEMISTRY MODULE BASED ON PAPUAN LOCAL WISDOM - Mamberuman Marthen Inggamer; Tiurlina Siregar (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2023)
This study aims to look at the Feasibility of mineral chemistry modules based on Papuan local wisdom by looking at the increase in learning outcomes using the module. The sample in this study was students in the fifth semester of chemistry education with a total of 18 people. The research results show that: 1). The feasibility of the module from the material validator obtained an average validation of 75.18% in the good category, the results of small-scale trials with an average percentage value of 81.75% in the very good category. 2). Increasing learning outcomes with an average n-Gain test of 0.55 in the moderate category, this indicates that in general the use of local wisdom-based modules can improve learning outcomes.